Pathways to school belonging. (5th July 2016) - Allen, Kelly; Boyle, Chris
Abstract : School belonging is generally regarded as a student's sense of affiliation or connection to his or her school. Anyone who has personally navigated the sometimes torturous terrain of secondary school is able to have some level of direct understanding of the importance that belonging, fitting in, and identifying with a school holds for most people. Educators and practitioners often work with young people who feel that they do not belong to the school community, in which they attend. An absence of belonging can manifest itself in mental health concerns, school attrition, and risk taking behaviours. Opportunities for early intervention through fostering school belonging are born from a greater understanding and awareness of what school belonging is and how it is contextualised and fostered. This special issue aims to place a focus on school belonging and highlight it as a significant social issue of our time.